Analysis of Organizational Culture and Innovative Work Behavior on Employee Performance at Lippo Mall, Palangka Raya City - Ferdinand (Indonesian Journal of Economic & Management Sciences, 2024)
Research in the field of human resource management to improve the performance of organizational culture and Innovative Work Behavior. A strong organizational culture gives employees a sense of identity and pride, increasing their motivation and engagement. A culture that supports collaboration and teamwork encourages employees to work together more effectively, share information, and support each other. This research was conducted quantitatively and distributed questionnaires to 100 respondents who were LIPPO MALL employees. The results of research from statistical analysis using SPSS 22.0, stated that 76% of the roles of organizational culture and Innovative Work Behavior in improving performance are very important. Employees involved in IWB tend to be more active in seeking and developing new ideas to improve processes, products, or services. The implications of the results can be to implement an organizational culture system and implement Innovative Work Behavior properly and correctly. Future research can adopt participative leadership to improve employee performance